Prospective development in diffusion barrier layers for copper metallization in LSI - Wong, H.Y.; Mohd Shukor, N.F.; Amin, N. (ELSEVIER SCI LTD, 2007)
The most recent development together with some challenging opportunities on barrier layers for copper metallization has been reviewed. This review study mainly focuses on the technology trends in interconnect metallization, with emphasis on barrier layer materials, mechanism that dominates diffusion in barrier layer materials, and promising candidate barrier layers for copper metallization in LSIs. The applicability of different materials as diffusion barriers in copper-based interconnects has also been assessed for practical usage. (C) 2007 Elsevier Ltd. All rights reserved.